Reliability and Validity of the PHQ-9 in Portuguese Women with Breast Cancer - Torres, Ana (2018)
Depression is often overlooked in oncology practice. Depressive module PHQ-9 was not studied in Portuguese cancer patients, despite its brevity and comparable psychometric proprieties to other depression scales. Which are the psychometric properties of the Portuguese version of the PHQ-9 for use with women with breast cancer? Reliability, sensitivity to change and the construct validity will be studied. The purpose of this study is to assess the psychometric properties of the Portuguese version of the PHQ-9 for use with women with breast cancer. This study intends to evaluate the reliability, the sensitivity to change and the construct validity of the PHQ-9 in a Portuguese Breast Cancer women sample. It was reproduced a principal component analysis and explored the reliability and validity of the questionnaire. The validation used a sample of 63 Portuguese women with breast cancer. A test-retest was conducted in 45 women, after 8 weeks. Construct validity was analyzed. PHQ-9 scores ranged from 0-27, with a mean score of 4,92 (SD= 4,63). The scale presented adequate internal consistency (α = .86) and test retest reliability (ICC= .87). It also presented good construct validity, as overall scores and severity levels were strongly associated with functional and symptoms subscales. The principal component analysis explains 48.42% of the variance. The validation process of the Portuguese PHQ-9 version shows metric properties similar to those in international studies, suggesting that it measures the same constructs, in the same way, as the original version. Data provided evidence for the validity of the PHQ-9 as a brief measure of depression severity in Portuguese women with breast cancer.